Research Methods in Health Communication: Principles and Application, 1st edition - Whaley, Bryan B. (Routledge, 2020)
This volume provides an essential roster of primary research methods as they apply to health communication inquiry. Editor Bryan B. Whaley brings together key health communication researchers to write about their primary methodological areas. Their chapters offer guidance and insights for a variety of approaches to answering research questions. The methods included here cover: